Microinsurance : What Can Donors Do? - Latortue, Alexia (World Bank, Washington, DC, 2012)
In most countries, reaching scale and providing real value to clients will likely require donor involvement in the medium term. Donors will need appropriate expertise and resources to engage effectively in micro insurance because it is relatively new, complex, and risky. Donors have diverse reasons for wanting to support micro insurance. Even within the same agency, different units may have varying views on how subsidies can be used best, how much clients should pay for insurance services, and what roles the government and the private sector should play. Strategic clarity on the reasons for engaging in micro insurance affects how a donor's objectives are set, how expertise is recruited, and what type of monitoring is implemented. There is still no consensus on what constitutes good performance for micro insurance programming. In part, this is simply because micro insurance is a relatively new area. To improve accountability for results, donors should agree up front on desired outcomes and performance. The Consultative Group to Assist the Poorest (CGAP) Working Group on Micro insurance's subgroup on performance indicators is leading efforts to define industry wide reporting ratios and, ultimately, to establish benchmarks. This work is essential to improve performance reporting and will help shape donors' performance agreements with partners.